Fostering Creative Thinking in Early Childhood: An Analysis of Developmental Stimulation - Nurjanah, Novita Eka; Yetti, Elindra; Sumantri, Mohamad Syarif (Universitas Pendidikan Ganesha, 2024)
Creative thinking skills in early childhood refer to the ability to generate new ideas, creative solutions, and view problems from different perspectives. These skills form an essential foundation for the development of a child's potential in the future. However, in practice, the development of creative thinking skills in early childhood is not adequately facilitated. This is primarily due to the lack of stimulation from the surrounding environment, leading children to become passive and less motivated to engage in creative thinking. This study aims to analyze and describe the level of creative thinking skills in 5–6-year-old children. The research method used is a survey of 147 children, with data collected through questionnaires completed by class teachers. The data were analyzed using descriptive quantitative techniques and presented in graphical form. The results show that, on average, the creative thinking skills of early childhood children in Surakarta are at the